COLLABORATION OF HOSPITAL MANAGEMENT AND COMMUNITY IN PREVENTION OF DIABETIC RETINOPATHY: STUDY OF COMMUNITY SERVICE PROGRAM AT UNDAAN EYE HOSPITAL SURABAYA - Dyah Kusuma Arnovita; Vip Paramarta; Kosasih; Fitriana (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to increase public awareness of DR prevention through education, screening, and training of health cadres. The methods used in this program include health education, interactive discussion sessions, and eye screening for participants at risk. The education was conducted in three sessions with a total of 150 participants consisting of diabetes sufferers, families, and the general public. Health screening involved 70 participants to detect the possibility of DR at an early stage. In addition, 10 health cadres were trained to assist in providing education to the surrounding community. The results of the program showed an 85% increase in participants' understanding of DR prevention based on a post-education survey. Although no DR cases were found in the screening, this activity still provided benefits in increasing public awareness of the importance of routine eye examinations. Health cadre training also had a positive impact by strengthening the role of the community in ongoing education. With a community-based approach and collaboration between hospitals and the community, this program is expected to contribute to reducing the incidence of DR and improving the quality of life of diabetes sufferers.